2014
DOI: 10.1007/s12013-014-9845-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Pretreatment Laboratory Parameters in Combined Small-Cell Lung Cancer

Abstract: Despite the increasing incidence of combined small-cell lung cancer (C-SCLC) in recent years, there have not been many data on clinical prognostic factors predicting prognosis of C-SCLC patients. In present study, we sought pretreatment features especially basic laboratory parameters predicting survival of C-SCLC. We analyzed 613 small-cell lung cancer (SCLC) patients at our institution between January 2005 and December 2010. We identified 114 patients with C-SCLC. The pathologic and clinical characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 23 publications
4
41
0
Order By: Relevance
“…However, the pretreatment PLR was not associated with OS (p = 0.101) or PFS (p = 0.182), which confirmed previous reports [20,24]. Additionally, as the other study reported, our study reconfirmed that extensive disease stage and performance status independently predicted OS (Table 4) [25].…”
Section: Discussionsupporting
confidence: 90%
“…However, the pretreatment PLR was not associated with OS (p = 0.101) or PFS (p = 0.182), which confirmed previous reports [20,24]. Additionally, as the other study reported, our study reconfirmed that extensive disease stage and performance status independently predicted OS (Table 4) [25].…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of C-SCLC was range from 2 to 45 % has been reported [8,16]. Interestingly, several studies found that if the SCLC patients have undergone surgery, more than 20-40 % had C-SCLC [5,8,17,18]. These studies reminded that, for the non-surgically managed patients, the diagnosis of C-SCLC was limited due to the small-size biopsy tissues.…”
Section: Discussionmentioning
confidence: 99%
“…PNI is not commonly used as a score for the measurement of systemic inflammatory responses, and a study of hepatocellular carcinoma (HCC) found that PNI was an independent and externally validated predictor of poor OS in patients with HCC (Pinato et al 2012). Only two studies have focused on the value of NLR for prognosis in SCLC, with the results indicating that elevated NLR could predict worse OS and PFS (Kang et al 2014;Wang et al 2014). There is, therefore, a lack of data from studies with adequate sample sizes and multiple inflammation-based scores.…”
Section: Discussionmentioning
confidence: 99%